Shock Index, Pediatric Age-Adjusted Predicts Morbidity and Mortality in Children Admitted to the Intensive Care Unit - Kuo-Chen Huang (Frontiers Media S.A., 2021)
Background: The shock index, pediatric age-adjusted (SIPA), defined as the maximum normal heart rate divided by the minimum normal systolic blood pressure by age, can help predict the risk of morbidity and mortality after pediatric trauma. This study investigated whether the SIPA can be used as an early index of prognosis for non-traumatic children visiting the pediatric emergency department (ED) and were directly admitted to the intensive care unit (ICU). We hypothesized that an increase in SIPA values in the first 24 h of ICU admission would correlate with mortality and adverse outcomes.Methods: This multicenter retrospective study enrolled non-traumatic patients aged 1–17 years who presented to the pediatric ED and were directly admitted to the ICU from January 1, 2016, to December 31, 2018, in Taiwan. The SIPA value was calculated at the time of arrival at the ED and 24 h after ICU admission. Cutoffs included SIPA values >1.2 (patient age: 1–6), >1.0 (patient age: 7–12), and >0.9 (patient age: 12–17). The utility of the SIPA and the trends in the SIPA during the first 24 h of ICU admission were analyzed to predict outcomes.Results: In total, 1,732 patients were included. Of these, 1,050 (60.6%) were under 6 years old, and the median Pediatric Risk of Mortality score was 7 (5–10). In total, 4.7% of the patients died, 12.9% received mechanical ventilator (MV) support, and 11.1% received inotropic support. The SIPA value at 24 h after admission was associated with increased mortality [odds ratio (OR): 4.366, 95% confidence interval (CI): 2.392–7.969, p < 0.001], MV support (OR: 1.826, 95% CI: 1.322–2.521, p < 0.001), inotropic support (OR: 2.306, 95% CI: 1.599–3.326, p < 0.001), and a long hospital length of stay (HLOS) (2.903 days, 95% CI: 1.734–4.271, p < 0.001). Persistent abnormal SIPA value was associated with increased mortality (OR: 2.799, 95% CI: 1.566–5.001, p = 0.001), MV support (OR: 1.457, 95% CI: 1.015–2.092, p = 0.041), inotropic support (OR: 1.875, 95% CI: 1.287–2.833, p = 0.001), and a long HLOS (3.2 days, 95% CI: 1.9–4.6, p < 0.001). Patients with abnormal to normal SIPA values were associated with decreased mortality (OR: 0.258, 95% CI: 0.106–0.627, p = 0.003), while patients with normal to abnormal SIPA values were associated with increased mortality (OR: 3.055, 95% CI: 1.472–5.930, p = 0.002).Conclusions: In non-traumatic children admitted to the ICU from the ED, increased SIPA values at 24 h after ICU admission predicted high mortality and bad outcomes. Monitoring the trends in the SIPA could help with prognostication and optimize early management.